Software design and data structures in turbo pascal - Koffman, Elliot B. (Addison-Wesley Pub, 1994)
This book uses Turbo Pascal to teach data structures and software engineering topics with an emphasis on data abstraction and the use of abstract data types. The book contains features like case studies, program style sections, syntax display boxes, common error sections, chapter reviews, quick-check exercises, and programming projects to aid in learning.